Nanocoating covalent organic frameworks on nickel nanowires for greatly enhanced-performance supercapacitors. (19th July 2017) - Han, Yang; Hu, Nantao; Liu, Shuai; Hou, Zhongyu; Liu, Jiaqiang; Hua, Xiaolin; Yang, Zhi; Wei, Liangming; Wang, Lin; Wei, Hao
Abstract: Nanocoatings of covalent organic frameworks (COFs) on nickel nanowires (NiNWs) have been designed and successfully fabricated for the first time, which showed greatly enhanced electrochemical performances for supercapacitors. The specific capacitance of electrodes based on as-fabricated COFs nanocoatings reached up to 314 F g −1 at 50 A g −1, which retained 74% of the specific capacitance under the current density of 2 A g −1 . The ultrahigh current density makes the charge–discharge process extremely rapid. The outstanding electrochemical performances of COFs nanocoating on NiNWs make it an ideal candidate for supercapacitors. And the nanocoating-design can also give a guidance for application of COFs in high-performance energy storages.